THE INTENSITY OF TIKTOK APPLICATION USERS TOWARDS THE CREATIVITY OF GENERATION Z IN JAKARTA - Purbaningrum, Maya; Andrini, Susi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The rapid proliferation of the TikTok application among Generation Z necessitates an exploration into its potential influence on their creative abilities, considering the platform's unique format and immersive engagement. This study aims to investigate the following questions: a) Does the intensity of TikTok application usage have an impact on creativity within Generation Z? b) To what extent does the intensity of TikTok application usage influence creativity in Generation Z? c) How does the TikTok application affect creativity within Generation Z? Drawing from Hovland's Stimulus-Organism-Response (S-O-R) theory, a mixed methods approach combining quantitative and qualitative descriptive methods is employed in the research methodology. The findings of this mixed methods study reveal that both quantitative and qualitative aspects contribute to the influence. In quantitative terms, both the intensity variable and creativity variable demonstrate validity and reliability. The coefficients of determination and significance signify a moderate effect size. This aligns with the qualitative findings, which emphasize that the intensity level among TikTok application users significantly impacts the creativity of Generation Z. This also addresses the question of the TikTok application's influence on creativity within Generation Z. In conclusion, this mixed methods approach underscores the complementary nature of the results, enhancing data comprehensiveness and offering supplementary insights.